PENINGKATAN KOMPETENSI BELAJAR INDUKSI MAGNET DAN ELEKTROMAGNETIK MELALUI PEMBELAJARAN KOOPERATIF BERBASIS PROBLEM POSING (Jurnal Inovasi Pembelajaran Karakter, 2023)
In learning Physics, students are often faced with materials that are abstract and verbal. The impact of these conditions causes students to be unable to understand the material, less active, creative, and unable to work on more varied questions. have an impact on learning outcomes that have not been completed. The goal to be achieved in this study is to apply problem posing cooperative models to increase the creativity of Magnetic and Electromagnetic Induction materials; describe the increase in results Classroom action research was carried out in two cycles. Each cycle consists of four stages, including preparation, action, training and evaluation, as well as reflection analysis. The first and second cycles consisted of three meetings The results of the action were able to increase the average creativity of students from a less average to very good. Acquiring the value of learning outcomes before the action averaged 66.91 which was completed only 50.00% increased the average value to 73.38 and which was completed 70.58% with KKM 75. After reflection in the second cycle, the learning outcomes at the end of the cycle test showed an increase in the class average of 78.08 and 88.23% completeness. From the results of the discussion it can be concluded that with problem posing-based cooperative learning the creativity of students increases, so that learning outcomes also increase.